PROGRAM PENGEMBANGAN KECERDASAN EMOSI SISWA BERBAKAT DI KELAS AKSELERASI SMA X MEDAN - Mahmudah, Rifaatul (2016)
Research design for development program of student emotional intelligence, specifically aimed to: (1) Determine the emotional intelligence of students; (2) Determine the distribution of emotional intelligence of students for each aspect; (3) Acquire the design program of emotional intelligence for gifted students. This research using quantitative and qualitative approaches. The research done in high school X Medan involving the vice principal, teachers, and a number of students as a data source. Data were collected through questionnaires and interviews. The results showed: (1) the emotional intelligence of students is in good category with a score of 3.35 (scale 84 of 100); (2) Aspects of the ability to manage emotions and empathy obtained a score of 3.3 (good). As for the aspects of self-awareness, the ability to use emotions productively and ability to build relationships obtained a score of 3.4 (good); (3) There are indications of problems that arise in the form of depression, excessive individualistic , lack of activity to facilitate the interest, talents and creativity of students, and excessive perfectionism (4) Programs compiled with the structure: title, background, objectives, materials, methods / strategies , time, and evaluation, to address the problems that arise. Keywords : Emotional Intelligence, Gifted students, Acceleration class Penelitian perancangan program pengembangan kecerdasan emosi siswa, secara khusus bertujuan untuk : (1) Mengetahui kecerdasan emosi siswa; (2) Mengetahui distribusi kecerdasan emosi siswa untuk masing-masing aspek; (3) Memperoleh program kecerdasan emosi siswa berbakat. Penelitian menggunakan pendekatan kuantitatif dan kualitatif. Penelitian di lakukan di SMA X kota Medan yang melibatkan wakil kepala sekolah, wali kelas dan sejumlah siswa sebagai sumber data. Data dikumpulkan melalui angket dan wawancara. Hasil penelitian menunjukkan: (1) kecerdasan emosi siswa dalam kategori baik dengan skor 3,35 (84 skala 100); (2) Aspek kemampuan mengelola emosi dan empati memperoleh skor 3,3 (baik). Sedangkan untuk aspek kesadaran diri, kemampuan memanfaatkan emosi secara produktif dan kemampuan membina hubungan memperoleh skor 3,4 (baik); (3) Ada indikasi masalah yang muncul berupa depresi, sifat individualis yang berlebihan, kurangnya wadah untuk penyaluran minat bakat dan kreativitas siswa, serta perfeksionisme yang berlebihan (4) Program disusun dengan stuktur : judul, latar belakang, tujuan, materi, metode/strategi, waktu, dan evaluasi, untuk menanggulangi masalah-masalah yang muncul. Kata Kunci: Kecerdasan emosi, Anak berbakat, Kelas akselerasi